Does auditor’s attributes impact on professional judgement in a financial audit? Empirical evidence from Myanmar SAI - Soe, Aye Khaing; Gavurova, Beata; Oláh, Judit; Hasan, Morshadul (Business: Theory and Practice, 2022)
This study investigates auditor attributes that may influence an auditor’s judgment in a financial audit. The purpose of this study is specified to show the impact of auditor’s attributes on professional judgment on the financial auditing process. An empirical research methodology is carried out to show the impact of the attributes on professional judgments. With this approach, hypotheses have been formulated and tested using empirical data and existing theories. A quantitative survey method was followed to collect the data for this study. A questionnaire was sent to selected auditors in Myanmar SAI to collect the data relating to the factors that influence auditors’ judgment, such as gender, age, education, knowledge, position level, experience, training, location, and job cognition. The findings of this study show that variables such as age, professional degree, education level, and knowledge are highly significant in auditor judgment. The limitation of this research is the sample size, and sample characteristics are different in Myanmar SAI from other SAIs. Almost 85% of respondents are female in Myanmar SAI. Therefore, it is considered a limitation of this study.